Achieving an Unpolitical "Political Education" by Means of Geography? A Historical Sketch - Schultz, Hans-Dietrich (Journal of Geography Education, 2016)
At the end of the 19th century the call for education for citizenship in school education became more and more heard. The contribution of the subject of geography depended on how it decided to deal with the consolidated scientific cultures that were characterized by a divide between the natural sciences concerned with nature and the humanities concerned with ideas including artefacts. Serving both cultures, the subject of geography had to decide to either accept the dualism or to bridge the dichotomy. The latter was the aim of regional geography, which was also supported by education policies. However, the path chosen mainly led from nature to spirit. Consequently geography's contribution to political education was seen in demonstrating, that all human life including politics was determined by the natural features on the surface of the earth, which should thus also be accepted as a normative guideline. Hence, by way of a naturalistic fallacy, it was concluded, that the being implied the norm and that politics was nothing but a way to translate natural norms into action without any recurrence to personal responsibility. The central means to promote this view was the map. Although today's scientific geography has dismissed the naturalistic view that claimed to be purely content-based, but was nonetheless biased, it still thrives in the realm of everyday knowledge. Disciplinary history can show the problematic implications of an approach that wants to deduce political decisions from physical objects, instead of understanding politics as interplay of spatial imaginations, political interests and claims to power.
Keywords: political education, regional geography, naturalistic fallacy, learning from history